2013
DOI: 10.1101/gr.166033.113
|View full text |Cite
|
Sign up to set email alerts
|

The genetic basis for individual differences in mRNA splicing and APOBEC1 editing activity in murine macrophages

Abstract: Alternative splicing and mRNA editing are known to contribute to transcriptome diversity. Although alternative splicing is pervasive and contributes to a variety of pathologies, including cancer, the genetic context for individual differences in isoform usage is still evolving. Similarly, although mRNA editing is ubiquitous and associated with important biological processes such as intracellular viral replication and cancer development, individual variations in mRNA editing and the genetic transmissibility of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 101 publications
1
23
0
Order By: Relevance
“…These findings are consistent with a recent report of editing variation in the AXB/BXA recombinant inbred panel (Hassan et al 2014). Of the remaining C-to-U editing sites, 11 show local genetic associations that map to the region of the edited gene.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…These findings are consistent with a recent report of editing variation in the AXB/BXA recombinant inbred panel (Hassan et al 2014). Of the remaining C-to-U editing sites, 11 show local genetic associations that map to the region of the edited gene.…”
Section: Resultssupporting
confidence: 92%
“…Another study found evidence of genetic variation for two (of 7389) A-to-I editing sites (Daneck et al 2012). Still another study found an association between RNA editing rates and genetic variation of Apobec1 (Hassan et al 2014). The broader impact of genetic variation on RNA editing in humans and mice remains unclear.…”
mentioning
confidence: 99%
“…S3). Additionally, we identified 10 transcripts with 68 C-to-U sites DRE between epileptic and control mouse hippocampus, which also included four C-to-U sites which had been previously reported as RNA-editing events in macrophages (Supplemental Table S2; Hassan et al 2014).…”
Section: Differential Rna-editing Analysis In Epilepsymentioning
confidence: 99%
“…In fact, it can be argued that the success of genetical genomics and its incorporation into the genetics of complex traits is largely due to the heritability of mRNA abundance, not to mention the simplicity of performing large-scale transcriptional analysis. Recently, we integrated isoform usage and linkage analyses in a genetically divergent set of recombinant inbred (RI) mice, and showed that isoform usage varies with both the macrophage genetic background and physiological state [9]. For instance, we observed that the C-type lectin domain family 7 member a (Clec7a or Dectin-1) gene, from which an alternative transcript that lacks the 4th exon can be produced [32], is differentially spliced in bone marrow-derived macrophages (BMDM) obtained from the classical laboratory inbred A/J (AJ) and C57BL/6J (B6) mice.…”
Section: Genetic Analysis Of Isoform Usage Can Facilitate the Identifmentioning
confidence: 99%
“…A major drawback to genetical genomics is that it presupposes that mRNA abundance represents the entirety of transcriptome complexity. Emerging empirical evidence indicates that several factors, such as alternative splicing (AS) and mRNA editing, not only contribute to transcriptome diversity but also are variable among individuals [9]. In fact, often protein abundance does not mirror the steady state transcript levels [10,11].…”
Section: Introductionmentioning
confidence: 99%